Socio-demographic determinants of alcohol consumption among young adults in Indonesia: A cross-sectional analysis of the 2023 Indonesian health survey - Wihatno, Elvianto; Asri, Yuni; Kushayati , Nuris; Murtiyani , Ninik; Ariyani , Anita Dwi; Fibriana , Linda Presti; Aprilin , Heti (UPPM STIKES Pemkab Jombang, 2025)
Alcohol consumption among young adults in Indonesia is a health problem that is influenced by sociodemographic factors. This study aims to analyze the sociodemographic characteristics of young adults in Indonesia and their association with alcohol consumption. The study design was cross-sectional with data from the 2023 Indonesian Health Survey (IHS). A total of 16,325 young adults aged 18-25 years were included in the study. The main variable analyzed was alcohol consumption. Socio-demographic characteristics such as age, gender, education level, marital status, region, employment status, and place of residence. The chi-square test and multivariate logistic regression were used to examine the relationship between independent variables and alcohol consumption. Significant associations were found between alcohol consumption and gender, education level, marital status and region. Men with lower education levels were more likely to consume alcohol. The highest proportion of drinkers was found in Java and Bali, especially in urban areas. Employment status showed no significant association with alcohol consumption. Socio-demographic factors significantly influence alcohol consumption among young adults in Indonesia. These findings highlight the need for public health strategies to address alcohol consumption. The importance of educational interventions and community-based programs to reduce the adverse effects of alcohol consumption.